Evaluation of NKp46 expression and cytokine production of decidual NK cells in women with recurrent pregnancy loss. (12th July 2022) - Yamamoto, Mayu; Fukui, Atsushi; Mai, Chuxian; Saeki, Shinichiro; Takayama, Ryu; Wakimoto, Yu; Yamaya, Ayano; Kwak‐Kim, Joanne; Shibahara, Hiroaki
Abstract: Purpose: NKp46, a receptor on NK cells, is involved in cytotoxicity and cytokine production. The authors aimed to evaluate the effect of NKp46 on decidual NK (dNK) cells during pregnancy and whether it can be a marker for immunological abnormalities in women with recurrent pregnancy loss (RPL). Methods: Flow‐cytometric analysis was made to assess NKp46 expression and intracellular cytokine production of dNK cells. The proportion of NKp46 + dNK cells was analyzed among RPL patients who aborted karyotypically normal pregnancies and those who either aborted karyotypically abnormal pregnancies or without genetic studies, and controls who were going through the induced abortion. Results: The % NKp46 + and %NKp46 bright dNK cells were significantly lower in the RPL women who aborted karyotypically normal pregnancies than in the control group. The %NKp46 bright dNK cells were significantly correlated with the NK1/NK2 ratio of dNK cells. The %NKp46 + dNK cell cutoff for RPL with immunological abnormalities was determined by the ROC curve analysis. In women with the low %NKp46 + dNK, NK1/NK2 ratios were significantly higher than those with the high. Conclusion: RPL patients with an immunological abnormality have decreased NKp46 expression and NK1 shift in dNK cells. NKp46 expression could be a marker for RPL of immunological abnormalities. Abstract : Women with recurrent pregnancy losses with karyotypically normal pregnancy, which suggests pregnancy loss with immune etiologies, have decreased NKp46 expression (Decidual NKp46 bright less than 70.9% and NKp46 + less than 86.5%) and NK1 shift in dNK cells. NKp46 expression could be a marker for RPL of immune etiologies.